Evaluation of the efficacy of a cannabidiol and cannabidiolic acid rich hemp extract for pain in dogs following a tibial plateau leveling osteotomy - Klatzkow, Sarah; Davis, Garrett; Shmalberg, Justin; Gallastegui, Aitor; Miscioscia, Erin; Tarricone, Jason; Elam, Lindsay; Johnson, Matthew D.; Leonard, Katelyn M.; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2023)
Objective: To determine the impact of a cannabidiol (CBD) and cannabidiolic acid (CBDA) rich hemp product on acute post-operative pain in dogs following a tibial plateau leveling osteotomy (TPLO), and to evaluate for changes in early bone healing, serum chemistry profiles, and complete blood counts. Methods: In this randomized, placebo controlled, blinded clinical trial, 44 client-owned dogs were assigned to receive either a CBD/CBDA product dosed at 2-2.5 mg/kg PO every 12 hours or a placebo for 4 weeks following a TPLO. Variables evaluated before (week 0), and at 2 and 4 weeks post-operatively included standardized veterinary assessments for pain score, weight-bearing, and lameness, the Canine Brief Pain Inventory (pain interference score – PIS, pain severity score – PSS), and serum biochemistry. Complete blood counts were performed at weeks 0 and 4. Additionally, orthogonal radiographs evaluating the degree of healing were taken at week 4. A mixed model analysis, analyzing changes of variables of interest from enrollment baseline to all other time points was utilized, with a p value < 0.05 considered significant. Results: Of the 44 enrolled patients, 3 were lost to follow up and excluded from analysis. No significant differences were noted between placebo (n=19) and CBD/CBDA (n=22) groups at any point in pain score, degree of lameness, degree of weight-bearing, PIS, PSS, or radiographic healing of the osteotomy. A significant finding of elevation of ALP above normal reference range in the treatment group was identified (p=0.02) and eosinophil count was affected by treatment (p=0.01), increasing from baseline in placebo and decreasing in treatment groups. Finally, a significant difference (p=0.03) was noted at 2 weeks post-operatively where 4 patients in the placebo group and no treatment patients received trazodone to facilitate activity restrictions. Clinical significance: Use of a CBD/CBDA rich hemp product dosed at 2-2.5 mg/kg PO every 12 hours did not have a significant impact on pain or delay early bone healing. A statistically significant increase in ALP, decrease in eosinophils, and reduced use of trazodone was identified in the treatment group.